COMPARISON OF FUNCTIONAL OUTCOMES BETWEEN OPEN REDUCTION AND INTERNAL FIXATION (ORIF) VERSUS MINIMALLY INVASIVE PERCUTANEOUS PLATE OSTEOSYNTHESIS (MIPPO) IN DISTAL TIBIAL FRACTURES (The Research of Medical Science Review, 2025)
Background: Distal tibial fractures are a common and challenging injury, often resulting from high-energy trauma or falls. They require effective treatment to restore function, prevent complications, and ensure long-term recovery. Objective: The objective of this study was to evaluate and compare the functional outcomes, including fracture healing, pain relief, complications, and recovery, of ORIF and MIPPO in patients with distal tibial fractures.Study Design and Setting: A prospective comparative study was conducted at DHQ Teaching Hospital Mirpur AJK. Methodology: The study involved 140 patients with distal tibial fractures, divided into two groups: 70 patients underwent ORIF, and 70 patients received MIPPO. Patients were randomly assigned to either the ORIF or MIPPO group. The fracture healing was assessed radiologically, and functional outcomes were evaluated using the American Orthopaedic Foot and Ankle Society (AOFAS) Ankle Hindfoot Score and Visual Analog Scale (VAS) for pain at 3, 6, and 12 months post-surgery. Complications such as infection, nonunion, malunion, and hardware-related issues were recorded.Results: The ORIF group showed a higher healing rate (93%) compared to MIPPO (86%). The ORIF group had better functional outcomes, with a higher AOFAS score, and showed greater pain relief at 12 months. The complication rate was also lower in the ORIF group (14%) compared to MIPPO (19%).Conclusion: ORIF demonstrated superior healing and functional outcomes compared to MIPPO in treating distal tibial fractures, though MIPPO remains a viable option with fewer surgical complications.